STUDENTS OF TEACHER EDUCATION IN HUNGARY BEFORE AND DURING THE BOLOGNA PROCESS - JANCSÁK, Csaba (Presa Universitară Clujeană, 2018)
In the past decade, several system-level changes have taken place in Hungarian higher education: university integration was realized, the credit system was introduced, the preselection-type admission system ceased to exist and teacher education was changed into a two-cycle education. New places of education and new, markedly different, forms of education have appeared, and the number of students admitted into institutes of higher education has increased significantly. The socio-politico-economic changes happening since the beginning of the 90s have made a significant impact on the world of public education as well (de-politicization of education, pluralism in selecting schools, decentralization of the administrative background of education, the formation of school autonomy, etc.). The drive behind these changes were the modern tendencies of economy and educational policy and, moreover, young people and their parents.